(NsONATY DLQ FORTEPIANO(B.s - (NwOLXFGANG aMADEJ mOCARTs; (Nk(B.(Na(B.(NmARTINSENAs (NREDAKCIQs; (Nw(B.(NwAJSMANAs (NREDAKCIQs ((NsANKT(B-(NpETERBURG(B.s (NlANX(B.s)
(NwELIKIJ AWSTRIJSKIJ KOMPOZITOR PISAL SONATY DLQ FORTEPIANO NA PROTQVENII WSEJ SWOEJ VIZNI(B.s
Keywords: (NFORTEPIANOs